2015
DOI: 10.1039/c4ta06087c
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic reactivity of {121} and {211} facets of brookite TiO2 crystals

Abstract: For the facet engineering of brookite TiO 2 , the surface atomic structure is known but the electronic structure has been rarely studied to date. Herein, we investigated both the surface atomic and electronic structure of brookite TiO 2 with various facets exposed. Theoretical calculations reveal that the {121} surface contains more undercoordinated Ti atoms and a higher surface energy than that of the {211} surface, and the experimental results show that brookite TiO 2 nanorods exposed with majority {121} fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 45 publications
3
39
0
Order By: Relevance
“…Several authors have pointed out an optimum ratios between anatase and brookite corresponding to the highest photoactivity in particular degradation processes [7,44]. On the other side, the nature of brookite-based photocatalysts is still matter of discussion, as pure brookite samples of different structures have been reported as both more and less active than other titania polymorphs or mixtures of brookite with other titania phases [5,14,15]. In photocatalytic degradation of alprazolam, presented in this work, the samples consisted of brookite-anatase mixed phase have shown increasing efficiency with decreasing of anatase in favor of brookite content.…”
Section: Assignmentioning
confidence: 98%
“…Several authors have pointed out an optimum ratios between anatase and brookite corresponding to the highest photoactivity in particular degradation processes [7,44]. On the other side, the nature of brookite-based photocatalysts is still matter of discussion, as pure brookite samples of different structures have been reported as both more and less active than other titania polymorphs or mixtures of brookite with other titania phases [5,14,15]. In photocatalytic degradation of alprazolam, presented in this work, the samples consisted of brookite-anatase mixed phase have shown increasing efficiency with decreasing of anatase in favor of brookite content.…”
Section: Assignmentioning
confidence: 98%
“…That is, the purpose of doping is relatively straightforward: modifying its large bandgap and electronic structure to optimize its optical properties for visible light harvest, improving each step in the charge kinetics to reduce the massive recombination of photogenerated carriers, and improving the interface and surface characteristics [16]. On the contrary, the photocatalytic activity depends strongly on the exposed crystalline faces [17,18]. Given that different crystal surfaces have different surface energy levels for the conduction band (CB) and valence band (VB), such differences in the energy levels will drive the electrons and holes to different crystal faces.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of surface energies of ten stoichiometric 1 × 1 low-index surfaces of brookite was calculated by first-principle density functional theory (DFT) simulations, showing that the electronic and chemical properties of brookite and the other TiO 2 phases can be significantly different [67]. Recently, combined theoretical and experimental studies of brookite nanomaterials demonstrated that preferential exposure of {121} faces, with under-coordinated atoms and lower VB potential, led to higher performance in photodegradation, while preferential exposure of {211} surface, with higher CB potential, resulted in enhanced H 2 productivity [71,72]. Such calculations also suggested that electrons struggle to migrate from bulk to {121} faces, in accordance for their poor H 2 production efficiency.…”
Section: Photocatalytic Studiesmentioning
confidence: 99%